The Influence Of AI-Based Marketing On Personalization And Automation Effectiveness In Digital Marketing Strategies: A Case Study Of Facebook Marketplace - Reza Hardian Pratama; Putu Eva Julianawati; Hiro Sejati; Sri Asmirani; Ahmad Sirfi Fatoni Sirfi Fatoni (Universitas Lembah Dempo, 2025)
This study investigates the impact of artificial intelligence (AI)-based marketing on the effectiveness of personalization and automation within digital marketing strategies, with a specific focus on Facebook Marketplace. As the use of AI technologies in targeted marketing efforts continues to grow, understanding their role in enhancing user experience and marketing efficiency becomes increasingly important. Employing a quantitative case study approach with a sample of 200 respondents, this research utilizes SEM-Smart PLS as the analytical tool. It explores how AI tools implemented by Facebook Marketplace—such as algorithm-driven product recommendations, automated customer interactions, and dynamic ad placements—contribute to more personalized consumer experiences and more efficient marketing operations. Data were collected from marketing professionals and users through interviews and surveys, providing insights into perceived benefits and challenges. The findings indicate that AI significantly enhances both personalization and automation, resulting in higher engagement rates and improved conversion efficiency. However, concerns related to data privacy and algorithm transparency remain prevalent. The study concludes with recommendations for marketers aiming to optimize digital strategies through AI while upholding ethical standards and maintaining user trust.